2017
DOI: 10.1021/acs.langmuir.7b00616
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of the Evaporation of Water at Low Pressures

Abstract: Although evaporation is considered to be a surface phenomenon, the rate of molecular transport across a liquid-vapor boundary is strongly dependent on the coupled fluid dynamics and heat transfer in the bulk fluids. Recent experimental thermocouple measurements of the temperature field near the interface of evaporating water into its vapor have begun to show the role of heat transfer in evaporation. However, the role of fluid dynamics has not been explored sufficiently. Here, we have developed a mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 60 publications
9
69
2
Order By: Relevance
“…Note the existence of the red layers below the green and blue layers below the interface. This phenomenon has also been observed in two dimensions by Song and Nobes [29] who performed planar PIV on the center plane of an evaporating water in the same cuvette used in this study and also by Li and Yoda [49] in the presence of buoyancy driven convection in a rectangular cavity and in a cylindrical tube in which 2D PIV was performed at the center of the tube during evaporation of water at low pressures [41]. However, the maximum velocity was detected to be exactly at the interface in the evaporation of methanol inside various size microtubes [33].…”
Section: The 3d Velocity Field Of An Evaporating Liquidsupporting
confidence: 82%
See 3 more Smart Citations
“…Note the existence of the red layers below the green and blue layers below the interface. This phenomenon has also been observed in two dimensions by Song and Nobes [29] who performed planar PIV on the center plane of an evaporating water in the same cuvette used in this study and also by Li and Yoda [49] in the presence of buoyancy driven convection in a rectangular cavity and in a cylindrical tube in which 2D PIV was performed at the center of the tube during evaporation of water at low pressures [41]. However, the maximum velocity was detected to be exactly at the interface in the evaporation of methanol inside various size microtubes [33].…”
Section: The 3d Velocity Field Of An Evaporating Liquidsupporting
confidence: 82%
“…To prepare the suspension for PIV experiments, one drop of high-concentration particle solution, which contained 2% V/V of 2.0 μm solid fluorescent microspheres (Fluoro-Max R0200, Thermo Scientific, Waltham, MA, USA ), was distributed in 40 mL of deionized water and mixed gently to achieve a uniform dilute suspension. For similar experiments in a cylindrical tube (Reference [41]), we showed that using a 100 times more dilute suspension did not change the flow pattern and the behavior of particle motions immediately below the interface. Therefore, we conclude that the measured velocity field does not change with concentration within the range of particle concentration that is commonly used in PIV experiments.…”
Section: Evaporation Experimentsmentioning
confidence: 61%
See 2 more Smart Citations
“…0.24 to 15.6 K). Kazemi et al [20] measured temperature discontinuity of 0.24 K at vapor pressure of 435 Pa and mass flux of 2.41×10 −4 kg/(m 2 s). In the experiments, there was no heating element in the vapor phase.…”
mentioning
confidence: 99%